Labor Motivation and its Endogenous Level - N. Scherbakov, V.; V. Dubrovsky, A.; V. Makarova, I.; I. Zotova, A.; E. Nakhratova, E. (International Journal of Engineering and Technology, 2018)
The article reveals key problems of motivational mechanisms that ensure economic growth, considering factor influences, including the endogenous level of a person. Efficiency of production and economic activity is considered from the viewpoint of revealing of the internal nature of person’s motivational interests. The article reveals general framework of labor motivation as a science of effective management of structurally connected technical and technological as well as organizational and economic structures, where the necessity for self-regulation of labor activity to build dynamic multilevel relations is justified. The endogenous level of motivational interests is considered through the prism of the integrity of personal development, where the supreme goal is not only political and economic interests, but also moral ones. Justifying the fundamental approaches to the labor management in terms of efficiency (optimality), very important is taking into account the potential opportunities, since from the perspective of optimal use of labor resources, development of economic potential is the determinative element in the achievement of the performance measure (economic value and benefit). The development of value orientations and performance indicators is exactly the way that allows reflecting the limitations of existing methodological approaches to the mobilization of labor resources in the mechanism of economic management. Considering a new approach to labor motivation from the perspective of organizational and economic science, the main mechanism, as a rule, is the principle of the maximum viability of a one or another labor process regulation system. An alternative to this approach can be only the socio-economic system that meets the principles of optimal construction of economic interests and evaluation of each element in the overall results of production activities. Bringing such an optimum control action is almost impossible without the regulatory role of the state, because the socio-psychological motives of behavior are the driving force of decisions made, and therefore cannot reveal the effectiveness of labor potential and its motivational component, which would contribute to the confirmation of the principles of rational labor construction. The basic principle of labor motivation from the standpoint of optimization should be the labor theory of value and utility as the basis of value and labor economic motivations, revealing the economic nature of costs and the function of economic value and utility at the endogenous level of social and labor relations.